2021
DOI: 10.1177/03635465211039865
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Microvascular Density of the Human Meniscus

Abstract: Background: The microvascular anatomy of the meniscus of the human knee is regarded as a crucial factor in the injury response. Previous studies have investigated the zone-dependent distribution pattern, but no quantitative data exist on vascular density and its age-related changes. Hypothesis/Purpose: The aim of the present study was to histologically analyze the vascular anatomy of the meniscus as a function of age. It was hypothesized that vascular density would decrease with increasing age. Study Design: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
4
12
1
1
Order By: Relevance
“…Qualitatively, the neonatal menisci showed greater branching and connectivity compared to adult menisci. Our findings are supported by previous cadaver studies measuring vascular density, where overall vascular density decreased with increasing age in human menisci 14,15,26,27 . In our study, the neonatal menisci were seemingly less wedge shaped and relatively thicker radially compared to the more normal, wedge-shaped adult menisci.…”
Section: Discussionsupporting
confidence: 91%
“…Qualitatively, the neonatal menisci showed greater branching and connectivity compared to adult menisci. Our findings are supported by previous cadaver studies measuring vascular density, where overall vascular density decreased with increasing age in human menisci 14,15,26,27 . In our study, the neonatal menisci were seemingly less wedge shaped and relatively thicker radially compared to the more normal, wedge-shaped adult menisci.…”
Section: Discussionsupporting
confidence: 91%
“…The search identified 411 articles, of which 352 were excluded based on title and abstract screening, and another twentyfive after full-text reading (Figure 2) [24]. Thirteen studies were included, which reported on patient characteristics affecting the microvasculature of the human meniscus (Table 1) [11][12][13][27][28][29][30][31][32][33][34][35][36], and another eleven studies reported on therapies enhancing the microvascularization of meniscal tissue (Table 2) [37][38][39][40][41][42][43][44][45][46][47]. Quality of the included studies, as assessed by the AQUA tool, is provided in Table 3.…”
Section: Literature Searchmentioning
confidence: 99%
“…Ten studies (3 HQ, 3 IQ, and 4 LQ) reported the effect of age on the microvascularization of the human meniscus (Table 1) [11][12][13][27][28][29][30][31][32]35]. Cadaveric studies have shown that the entire meniscus is vascularized around birth, but with increasing age, the vascularity gradually decreases from the inner to the peripheral margin [11,28].…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…In 2022 the understanding of the meniscus anatomy [9], biomechanics [10], and pathologies is certainly at the forefront of orthopaedic discussions. In terms of anatomy, numerous ligaments attaching the meniscus to the tibia have been highlighted.…”
Section: Meniscusmentioning
confidence: 99%